Design for manufacturing of custom-made femoral stem using CT data and rapid prototyping technology. (17th June 2011) - Abbaszadeh, Farid; Rahmati, Sadegh; Kheirollahi, Hossein; Farahmand, Farzam
Rapid prototyping (RP) applications have an increasing trend, making the future of RP more and more promising. These applications may include design, development, and manufacture of medical devices and instrumentation, as well as prosthesis design, anatomical modelling, surgical planning and prosthesis fabrication. This paper provides a new methodology for design of custom-made femoral stem, providing high accuracy of femoral canal reconstruction via 3D modelling of femoral stem with optimal fill and fit. The result of this methodology is optimised load transfer, minimum stem micromotion, increase in initial stability and extended durability. In addition to the above, the possibility of combining the stem with different modular necks to satisfy any type of femoral head shapes and facilitating the communication between designer and surgeon are other advantages. Applying RP technology has facilitated manufacturing of complex 3D femoral stems and has lead into time and economical benefits.